13 Coordinate my care: increasing prevalence among COPD patients. (12th November 2018) - Ridgley, Joanne; Gupta, Tanya; Burrows, Abigail; Gough, Nicholas
Abstract : Backgrounds: Coordinate My Care (CMC) is a London-based initiative which aims to make patient advanced care plans (ACP) accessible across trusts and within the community. Established in 2012, CMC is a relatively new form of ACP and although evidence indicates high useage by paramedics, CMC frequency among patients with life-limiting conditions is low. Aims: We aimed to implement a series of system-based changes to increase the number of CMC records from 22% to at least 50% among chronic obstructive pulmonary disease (COPD) patients known to the Integrated Respiratory Team (IRT) who were nearing the end of life. Methods: We implemented two Plan, Do, Study, Act cycles (PDSA) based on discussions with IRT. Throughout the first PDSA cycle we introduced a palliative care nurse at weekly IRT meetings to facilitate discussion of CMC. During PDSA cycle two we ensured that patient specific pathways (PSPs), a form of ACP kept by the patient in case of emergency, were uploaded onto CMC. Results: Over 12 weeks, we increased the percentage of patients with CMC records to 24.4% after PDSA cycle 1% and 34.2% after PDSA cycle 2 (increase of 2.4% and 12.2% from the baseline respectively). Discussion: Whilst keeping a palliative care nurse in IRT meetings may not be a long-term, maintainable, cost-effective intervention, we hope that uploading PSPs onto CMC will be a sustainable change as it is low-cost and time efficient. Making these procedural changes through identifying problems within the team, we hope that these initiatives could be applied to a wider patient population.